A simple rapid technique for detection of palm oil in ghee - Ramani, Akshay (Indian Journal of Dairy Science, 2019)
The detection of palm oil adulteration in ghee continues to be a challenge for the dairy industry as well as food testing laboratories. Recently, various sophisticated instrument based protocolsÂ have been developed to detect a low level of vegetable oil in ghee but applications of those techniques in Indian condition is still a challenge, due to lack of modern instrument equipped food forensic lab facilities. Hence simple and rapid tests are very much essential to ascertain the quality of ghee. In the present investigation, a rapid chromogenic test based methodology has been standardized to detect palm oil in ghee. This standardized protocol did not show any false positive results in the genuine ghee samples. Adulteration of ghee with palm oil at the 5% level could be detected using the standardized chromogenic test. The protocol standardized is rapid and convenient to use.